Formation of the Psychological Readiness of Climbers for Responsible Competitions - Alexander Piratinsky; Maya Piratinskaya; Valerii Malkin; Dmitry Sharafutdinov, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
This paper looks into the problem of bringing top athletes to the peak of mental readiness for important competitions. The technique of preparation of athletes-climbers for responsible competitions is presented that would facilitate the formation of coping strategies. Among the respondents were members of the national team of Russia in climbing when preparing and competing in European and world championships and cups. The technique presented here allowed us to gradually bring top athletes to optimal mental readiness for important competitions, which ensured their consistent and successful performance in championships and cups of Russia, Europe and the whole of the world.